Decriminalizing Payment of Gamete Donors and Surrogates in Canada: An Analysis of Factors Influencing the Public Debate in Light of Bill C-404 - Anne-Isabelle Cloutier (McMaster University Library Press, 2019)
On 29 May 2018, the Liberal MP Anthony Housefather tabled Bill C-404 titled An Act to amend the Assisted Human Reproduction Act which seeks to decriminalize the payment of gamete donors and surrogates across Canada. Although Prime Minister Justin Trudeau indicated the importance of having a societal debate on the subject, the bill was read only once by the House of Commons before it died on the Order Paper. Bill C-404 aimed to increase the number of Canadian gamete donors and surrogates to fulfill Canada's domestic needs, which are purportedly not being met because of a lack of economic incentives on the supply side and the existence of a grey market that deters some Canadians in acting as donors or surrogates and causes intending parents to fear being criminally sanctioned if the reimbursement they pay is deemed unrelated or unreasonable. While Bill C-404 has not been adopted by Parliament, this paper seeks to analyze the policy tensions at the heart of the decriminalization of payment of donors and surrogates-tensions that may well resurface in the future. As long as the alleged shortage of donors and surrogates persists, stakeholders are likely to continue to advocate for legislative change.